A Note on the Pathogenicity of Metarhizium anisopliae (Metschnikoff) Sorokin on Larvae of Schizonycha sp. (Coleoptera: Scarabaeidae) (University of Khartoum Journal of Agricultural Sciences, 2025)
An experiment was conducted in the laboratories of the Research Departmentof Kenana Sugar Company during 2004/2005 season to study the efficacy ofMetarhizium anisopliae as a pathogen against the white grub Schizonycha sp. The funguswas isolated from a dead larva of white grub found in the root zone of a sugarcane plant.It was cultured in the laboratory and used to inoculate healthy larvae of Schizonycha sp.The typical symptoms of mycosis disease were observed two days after inoculation.Death started on the third day and 94.3% of the population were killed within two weeksat 27ºC and 92% RH. Percentage of mortality and days after inoculation were highlyassociated with a positive linear relationship
Keywords: Sugarcane; Metarhizium anisopliae; Schizonycha sp; mycosis; mortality